Participation Questionnaire for Preschoolers With Autism Spectrum Disorder: Item Development - Takuto Nakamura; Sakumi Koyama; Hirofumi Nagayama; Satoshi Sasada (Hindawi-Wiley, 2024)
Occupational therapists need to comprehensively assess the participation of children with autism spectrum disorder (ASD) in daily activities and evaluate the effectiveness of relevant interventions. Several participation measurement tools have been developed for children with ASD, but these tools require expert involvement, which is a barrier to large-scale surveys. To address these concerns, a caregiver-administered questionnaire-the Participation Questionnaire for Preschoolers (PQP)-was developed. However, this tool could be improved due to its narrow age range of 48-72 months and because the item development process does not reflect the perspectives of children and caregivers. Therefore, we expanded the PQP's target age range to 36-83 months and developed new items that reflect the perspectives of professionals and caregivers. Interviews were conducted with eight experts in supporting children with ASD and 11 caregivers of children with ASD. The interviews were transcribed, and a content analysis was performed. The number of questions was reduced from 51 to 36, and the order of items was changed for clarity. Two of the eight subdomains were removed to clarify the conceptual difference between activity and participation. The updated version of the PQP has two unique features: (1) it can be administered without expert involvement, and (2) it includes items specific to the challenges faced by children with ASD. Future development of the scale and validation of its measurement properties are needed.